Robust Aggregated Hierarchical Sliding Mode Controller Based on the High-Gain Observer of Double-Pendulum Overhead Crane - Bidane Issam; Ailane Abdellah; Khamlich Salaheddine (EPJ Web of Conferences)
This study presents a control system for an overhead crane using an aggregated hierarchical sliding mode control (AHSMC) approach with a high-gain observer. The control law is designed to minimize oscillations and increase the stability of the crane system. The observer is used to estimate the state of the system, including the cable angle and payload (spreader and container) angle, using only the available sensor measurements. The proposed approach was tested through simulations, demonstrating its effectiveness and robustness in the presence of changing reference signals. The results show that the proposed control system provides accurate and stable control of the overhead crane system with improved static and dynamic performance.